Laser Transfer and Firing of NiV Seed Layer for the Metallization of Silicon Heterojunction Solar Cells by Cu‐Plating. Issue 8 (10th July 2017) - Rodofili, Andreas; Wolke, Winfried; Kroely, Laurent; Bivour, Martin; Cimiotti, Gisela; Bartsch, Jonas; Glatthaar, Markus; Nekarda, Jan
Abstract : We present a laser‐based method for the metallization of silicon heterojunction solar cells by Cu‐plating. It consists of first applying a dielectric layer on the transparent conductive oxide (TCO) as a plating mask. Then, a NiV seed is transferred by laser induced forward transfer (LIFT) from a plastic carrier foil onto the wafer. In the second laser step, the NiV layer is fired through the dielectric layer to form a contact to the TCO. After the laser process, Cu‐fingers are produced by plating. The dielectric plating mask remains on the cell. Parasitic plating is prevented by using an advanced reverse pulse plating process. With the first solar cells we reach a maximum efficiency of 22.2% and an efficiency gain of 0.5%abs compared to low‐temperature screen printing reference cells, due to a higher short circuit current and fill factor. The 30 μm wide fingers reach specific contact resistances down to 0.6 mΩ cm 2 and also, pass a tape adhesion test. We further demonstrate that the laser process does not cause any measurable open circuit voltage loss and that a precise alignment of the two laser steps is not necessary. Abstract : A new method for the metallization of silicon heterojunction solar cells by Cu‐plating based on laser induced forward transfer (LIFT) is presented. With the first solar cells, a maximum efficiency of 22.2% and an efficiency gain of 0.5%abs compared to low‐temperature screen printing reference cells is reached, due to a higher short circuit current and fill factor.